The Popularity of Waranggana Tayub Malang through Body Exploitation - Hidajat, Robby (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2014)
Tayub is a ronggeng type of dance performance. It is widely performed in Javanese regions.Originally, Tayub functioned as a fertility ritual; then it developed as entertainment. The growth of Tayub in Malang in the 1950s was intended for identity and the main dancer called tandak was changed to Waranggana. As a result, there was a transformation in the form of the dancer’s body: (1) exploring body-initiating identity, (2) manipulating the body through magical effect, and (3) body consumptive economization and love ruse. The qualitative method was used with an art phenomenological model in this study. The data were collected using interview and observation methods and was analyzed interpretatively. The result of the research was that female body interpretation is politicized to survive creatively, in order to maintain popularity and to support the lifestyle of the artist.